Dialektika Induksi dan Deduksi dalam Pemikiran Hukum Islam - Mun’im, Abdul (ISLAMICA: Jurnal Studi Keislaman, 2009)
Modern science requires that dialectic between induction and deduction should take place so that development of knowledge and its promotion may be acquired. In modern sciences in other words, such dialectic constitutes the very condition for the creation and invention of new theories, discoveries and fields of knowledge. This paper is trying to argue that as a science, fiqh in one way or another has appropriated a similar route of using these two methods of induction and deduction in its process to extrapolate religious laws and rules.We argue that in fiqh induction produces norms that may serve as the foundation for the deductive method. We contend that induction is a general rule extracted directly from the first source of Islamic law, namely revelation, whereas deduction is the legal principles (alqawaâid al-fiqhiyyah) that the ulama formulated on the basis of their understanding on the contents of revelation.